A Composite Elastic Conductor with High Dynamic Stability Based on 3D‐Calabash Bunch Conductive Network Structure for Wearable Devices. (28th June 2018) - Yu, Zhe; Shang, Jie; Niu, Xuhong; Liu, Yiwei; Liu, Gang; Dhanapal, Pravarthana; Zheng, Yanan; Yang, Huali; Wu, Yuanzhao; Zhou, Youlin; Wang, Yuxin; Tang, Daxiu; et al.
Abstract: As an indispensable basic component of wearable devices, the composite elastic conductor is widely used for elastic electrode and elastic wire. The ideal elastic conductor is expected to have high conductivity and stretchability, and maintain the resistance constant during stretching. However, it's difficult for the current composite elastic conductors filling solid conductive materials. Here, a composite elastic conductor filling liquid‐metal alloy is reported. Highly conductive and freely deformable liquid‐metal filler achieves the elastic conductor with excellent conductivity and stretchability (electrical conductivity of 1.34 × 10 3 S cm −1, sheet resistance of 17.59 mΩ □ −1, and breaking elongation of 116.86%). Importantly, the filler forms novel three‐dimensional Calabash Bunch conductive network structure in elastic matrix, which enables the elastic conductor to have excellent dynamic stability during stretching. The relative resistance variation is only 4.305% at 116.86% strain. This variation is 2–5 orders of magnitude smaller than that of the reported composite elastic conductor at the same strain, which is important for wearable devices to remain performances fairly unchanged undergo large deformation. Finally, it served as elastic electrodes of a stretchable capacitive strain sensor and elastic wires of a stretchable earphone respectively to demonstrate its potential in wearable devices. Abstract : A liquid‐metal‐based composite elastic conductor with 3D‐Calabash Bunch conductive network structure is prepared by compositing the liquid‐metal alloy galinstan with the polydimethylsiloxane. It not only achieves high conductivity and high stretchability simultaneously, but also significantly improves the dynamic stability, which is critical for applications in the wearable electronic devices as elastic electrodes and elastic wires.